Understanding the Role of Users’ Psychological Needs on Relationship Quality in Short Video Applications - Huangfu, Zhounan; Zhou, Lei; Zhao, Jing; Kotchasit, Sombat; Chen, Wanmei (Frontiers in Psychology, 2022)
Along with the rapid development of big data, artificial intelligence and information technology, the relationship quality between short video applications and users is important for the sustainable development of short video applications. However, the existing studies have explored the mechanism of the role of relationship quality in a limited way. In order to respond to this critical issue, this study constructs a theoretical model based on attachment theory and combined with self-determination theory, with autonomy needs, competence needs and relationship needs as influencing factors, emotional attachment as mediating variables and relationship quality as outcome variables, and the moderating role of attachment anxiety in which this study also analyze the mechanism of short video applications users' psychological needs on relationship quality by combining the moderating role of attachment anxiety. In this study, a sample of 512 university students using short video applications was used. The results of the data analysis indicated that emotional attachment was significantly influenced by psychological needs played a positive role in relationship quality and mediated the relationship between psychological needs and relationship quality. The results of further analysis also revealed that attachment anxiety plays a moderating role in the relationship between emotional attachment and relationship quality. This study examines the intrinsic mechanism by which psychological needs affect relationship quality through emotional attachment, reveals the practical effects of short video applications users' sustained use behavior, and provides a reference for innovative management and business practices of short video applications.